2018
DOI: 10.1080/09537104.2018.1466386
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia-associated atherogenic oxidized lipids induce platelet hyperactivity through phospholipase Cγ2-dependent reactive oxygen species generation

Abstract: Oxidized low-density lipoprotein (oxLDL) and associated oxidized phosphocholine-headgroup phospholipids (oxPCs) activate blood platelets through ligation of the scavenger receptor CD36. Previously, we found that oxLDL stimulated phosphorylation of phospholipase Cγ2 (PLCγ2). However, the functional relevance of PLCγ2 phosphorylation in oxLDL-mediated platelet hyperactivity remained elusive. Here, we set out to explore the functional importance of PLCγ2 in oxLDL-mediated platelet activation using human and genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In the CNS, PLCG2 was mainly expressed on microglia, but was also expressed on neurons in the granulosa cell layer of the dentate gyrus [ 61 ]. PLCG2 is involved in alleviating ROS levels and is closely associated with OS [ 26 , 27 ]. Other studies found that PLCG2 regulated mTOR through the diacylglycerol/protein kinase C signaling branch, thereby affecting the proliferation and apoptosis of B cells [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CNS, PLCG2 was mainly expressed on microglia, but was also expressed on neurons in the granulosa cell layer of the dentate gyrus [ 61 ]. PLCG2 is involved in alleviating ROS levels and is closely associated with OS [ 26 , 27 ]. Other studies found that PLCG2 regulated mTOR through the diacylglycerol/protein kinase C signaling branch, thereby affecting the proliferation and apoptosis of B cells [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that PLCG2 phosphorylation induced by the CSF1R activation could increase the rapid release of Ca 2+ in monocytes and promote the differentiation of monocytes [ 25 ]. PLCG2 is expressed on microglia and neurons in the CNS and is involved in regulating OS [ 26 , 27 ]. PLCG2 activates the cyclic adenosine monophosphate- (cAMP-) response element-binding protein through activation of the Ca 2+ signaling pathway induced by protein kinase A (PKA) [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with canonical signalling from GPVI, SFK couple CD36 to the activation of Syk, which leads to the activation of a RhoA-dependent inhibition of myosin light chain phosphatase that underpins spreading and shape change [ 46 ]. Downstream signalling from Syk leads to phosphorylation of phospholipase Cγ2 (PLCγ2), which appears to be critical for oxLDL-induced platelet activation, since either pharmacological inhibition or genetic deletion blunted platelet hyperactivity [ 46 , 89 , 140 ]. The role of Syk in activating the other key signalling elements, such as ERK, p38, Mkk4/JNK, and Vav1/3, is unclear; although, it is likely, given that Syk activation lies downstream of other tyrosine kinase-linked receptors in platelets, for example, GPIb-IX-V, GPVI, Clec-2, and α IIb β 3 [ 141 , 142 , 143 , 144 ].…”
Section: Scavenger Receptors—the Transducers Of Oxldl Into Platelet H...mentioning
confidence: 99%
“…Nox2 inhibition also improved hind-limb blood flow in mice, reducing ROS level and inflammation after TNF-α administration [ 274 ]. Besides, NOX-2 inhibitor gp91ds-tat, combined with the ROS scavenger N-acetyl-cysteine (NAC), has proven to be effective against platelet activation induced by prolonged exposure to oxLDL-associated oxidized phospholipids [ 275 ]. GLX351322, a selective inhibitor of NOX4, has been suggested to be effective in T2D [ 276 ], while Plumbagin, another Nox4 specific inhibitor, has been reported to counteract oxidative stress-induced endothelial dysfunction and preadipocyte apoptosis under hyperinsulinemic conditions [ 277 , 278 ].…”
Section: New Therapeutic Approaches Targeted Endothelial Dysfunctimentioning
confidence: 99%